The study of glycerol plasticized thermoplastic sago starch - Ahmad, Zuraida; Abdul Razak, Nur Humairah; Abdul Wahid, Nur Izwah; Zulkifli, Siti Naqiah (Trans Tech Publications, Switzerland, 2012)
Thermoplastic sago starch (TPSS) was produced by plasticizing with glycerol through melt blending before being compression moulded. The investigated TPSS was prepared at glycerol/starch weight fraction of 40/60, 35/65 and 30/70. The functional groups composition, tensile strength, density, moisture content and water absorption were evaluated and compared at different glycerol/starch ratio. The compatibility of the glycerol as the plasticizer in the TPSS was proven by Fourier transform infrared spectroscopy (FTIR) where glycerol could form stable hydrogen bond with sago starch. This preliminary study demonstrated that the stress at maximum load was only applicable for lower glycerol/starch ratio of 30/70. The density of TPSS was inversely proportional to the increment of glycerol/starch ratio whereas moisture content and water absorption had opposite relationship.